Penerapan Terapi Aktivitas Kelompok Mengenal Halusinasi pada Gangguan Sensori Halusinasi Pendengaran: Application of Group Activity Therapy to Recognize Hallucinations in Sensory Stimulation Disorders: Auditory Hallucinations - Dewi Pratiwi; Indri Iriani; Maryam (Jurnal Kolaboratif Sains, 2023)
Mental disorders are serious mental health problems that cause cognitive and effective disturbances and hinder social functioning so that individuals are unable to carry out their daily activities. Hallucinations are perceptual distortions that are not real and occur in maladaptive neurobiological responses. The purpose of this study is to describe the application of group activity therapy "knowing hallucinations" in patients with sensory stimulation disorders: auditory hallucinations in the Srikaya Room, Madani Regional General Hospital, Central Sulawesi Province. The case study design used is a descriptive type of research with a case study approach. The subject of this case study is a patient with sensory stimulation disorder, auditory hallucinations who has participated in group activity therapy in the Srikaya Room at Madani Hospital, Central Sulawesi Province. The results of research conducted on patients Mr. R with Sensory Stimulation Disorder, in this study one diagnosis was found, namely Schizophrenia. After nursing care for 3x24 hours, the patient can recognize the hallucinations he is experiencing, can control the hallucinations by scolding, conversing with others and carrying out scheduled activities.